Farmers' field days focused on rice-maize systems - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Three farmers field days conducted in 2011 at 3 project sites in Bangladesh. More than 100 farmers, government extension personnel, researchers, project staff, and visited sites that feature farmers’ participatory conservation agriculture (CA)-based unpuddled transplanted rice (UPTR), zero-tillage direct-seeded rice (DSR) trials, and Nutrient Manager (NM) for rice trials. Activities on CA practices and site-specific nutrient management (SSNM) for rice and maize in rice-maize (R-M) systems.